2020
DOI: 10.2478/fon-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mindfulness meditation on anxiety, depression, stress, and mindfulness in nursing students: a meta-analysis and trial sequential analysis of randomized controlled trials

Abstract: ObjectiveThe aim of this study was to assess the effectiveness of mindfulness meditation (MM) on anxiety, depression, stress and mindfulness in nursing students.MethodsA comprehensive search and screening procedures were conducted to locate all MM interventions implemented with nursing students. For randomized controlled trials (RCTs) in accordance with the inclusion criteria, a search was conducted in PubMed, Embase, Web of Science, Medline, PsycINFO, Cumulative Index to Nursing and Allied Health (CINAHL), Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
17
0
2
Order By: Relevance
“…Based on the results of the current study, it is recommended clinicians continue using resilience resources in their work with university students. Other researchers found mindfulness effective on reducing levels of stress, anxiety, and depression (Khoury et al, 2015 ; Li et al, 2020 ). Based on the findings of this study, clinicians may also want to include teaching mindfulness and utilization of mindfulness related practices when working with university students coping with COVID-19 fear, depression, anxiety, and stress as well to enhance students well-being.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the results of the current study, it is recommended clinicians continue using resilience resources in their work with university students. Other researchers found mindfulness effective on reducing levels of stress, anxiety, and depression (Khoury et al, 2015 ; Li et al, 2020 ). Based on the findings of this study, clinicians may also want to include teaching mindfulness and utilization of mindfulness related practices when working with university students coping with COVID-19 fear, depression, anxiety, and stress as well to enhance students well-being.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, mindfulness should be taken into consideration for decreasing negative effects of COVID-19 pandemic. As literature reviews have suggested, mindfulness practices are effective on coping with stress, anxiety, and depression; therefore, individuals may practice mindfulness to cope with presenting negative symptoms during the global COVID-19 pandemic (Behan, 2020 ; Khoury et al, 2015 ; Li et al, 2020 ). With support for this idea, Behan ( 2020 ) reviewed the benefits of meditation and mindfulness practices, and recommended utilizing such tools to help enhance coping skills of individuals in this difficult time.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that meditation was an effective intervention for nursing students to decrease their stress and anxiety and could be used to manage stress in student nurses [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes from a meta-analysis may include a more precise estimate of the outcomes, than any individual study contributing to the pooled analysis. The examination of variability or heterogeneity in study results is also a critical outcome [6,9]. The benefits of meta-analysis include a consolidated and quantitative review of a large, and often complex, sometimes apparently conflicting, body of literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent decades many researches proposed MBSR as a potential tool helping practitioners of becoming less vulnerable to stressors, Burnout as well as improving resilience and self-compassionate [4][5][6][7]. However, recent studies show inconclusive results about this association meta-analysis based on RCTs n this era [7,8,9], furthermore most of the trials done on the non-clinical setting ,yet only limited research done on clinical population [8,9]. Therefore, to help to ensure health care providers and patient safety, we used the data published RCTs in the last 10 years to carry out a meta-analysis with the main aim to Evaluate the effectiveness of Mindfulness -Based stress reduction intervention in promoting health care professional's mental health and wellbeing in terms of stress reduction, Burnout and level of satisfaction.…”
mentioning
confidence: 99%